If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -3x + -7 = 23 + -6x Reorder the terms: 15 + -7 + -3x = 23 + -6x Combine like terms: 15 + -7 = 8 8 + -3x = 23 + -6x Solving 8 + -3x = 23 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 8 + -3x + 6x = 23 + -6x + 6x Combine like terms: -3x + 6x = 3x 8 + 3x = 23 + -6x + 6x Combine like terms: -6x + 6x = 0 8 + 3x = 23 + 0 8 + 3x = 23 Add '-8' to each side of the equation. 8 + -8 + 3x = 23 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = 23 + -8 3x = 23 + -8 Combine like terms: 23 + -8 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 5(k-2)-4(k-1)=6 | | 12t-4(t-6)=32 | | 2*(3+1)=5X+7 | | (-8)=x^2+8x+9 | | cosx-tgx=0 | | (x^2-4y^2/x^2xy^2) | | 3r^2-10r=-10 | | t^-1/3=1/2 | | 4(4x+3)-6(x+3)=5x-11 | | F(x)=3x^2-2x+100 | | 3x+14=2x+17 | | 10-3y=-20 | | 4^(2x)=(13/10) | | 3x+1-3=17 | | 5[t+2]=-5 | | [a-11]*7=42 | | 2[3s+8]=82 | | 3y-12xy+4x=0 | | 4[2l+6]=64 | | 7log(3x)+elog(5x)=15 | | 5[a-9]=65 | | [u+2]*7=49 | | [q-3]*4=36 | | [e+5]*5=35 | | X^4=1/9 | | 8x+4=6-2x-4 | | 5(x-8)+5=3(x+4)-7 | | 4x+2+3+0.7=20 | | 125x^4+x=0 | | 2x+14x=9 | | 6x+6=-50+2x | | 25x^2-50y+72=0 |